FIGO consensus guidelines on placenta accreta spectrum disorders: Nonconservative surgical management (VITAE Academia Biomédica Digital, 2018)
For more than half a century after the first case series of placenta accreta was reported in1937,1 the main and often only approach to management was a cesarean hysterectomy. Thisapproach had the advantage of reducing the immediate risks of major hemorrhage associatedwith accreta placentation at a time when there was no access to blood transfusion.Over the last two decades, a variety of conservative options for the management of placentaaccreta spectrum (PAS) disorders have evolved, each with varying rates of success, and peripartum and secondary complications.2–4 In a recent systematic review and meta- analysis of the outcome of placenta previa accreta diagnosed prenatally, 208 out of 232 (89.7%) cases had an elective or emergent cesarean hysterectomy.5 As a result of a lack of randomized clinical trials, the optimal management of PAS disorders remains undefined and is determined by the capacity to diagnose invasive placentation preoperatively, local expertise, depth of villous invasion, and presenting symptoms.4In cases of high suspicion for PAS disorders during cesarean delivery, the majority of membersof the Society for Maternal- Fetal Medicine (SMFM) proceed with hysterectomy and only 15%–32% report conservative management.6,7However, there is considerable practice variation reported on aspects of care aroun delivery andhysterectomy by both obstetricians and maternal- fetal medicine specialists.6,8